Pharmaco-Toxicology Research Laboratory (PTRL) advanced research facilities and services at PTRL / Mohd Alimukhti Mansor and Gurmeet Kaur Surindar Singh - Mansor, Mohd Alimukhti; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
Pharmaco-Toxicology Research Laboratory (PTRL) operates as an integral component of the Department of Pharmacology and Pharmaceutical Chemistry at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Selangor, Puncak Alam Campus. Situated on level 6 of the FF3 Building, PTRL is dedicated to providing a comprehensive range of services and facilities tailored to meet the diverse needs of researchers. The laboratory offerings encompass an extensive suite of capabilities, including extraction methodologies, antioxidant activity studies, plant culture techniques, cell signalling investigations, polymerase chain reaction (PCR) work, western blotting procedures, stem cell research, chromatography analyses, flowcytometry applications, imaging technologies, freeze-drying of samples and precise evaluation of animal activity parameters. Moreover, alongside this comprehensive range of laboratory equipment, PTRL takes pride in extending its facilities to accommodate an array of specialised research studies. These include plant tissue culture studies, investigations into fungus and bacteria, exploration of natural herb extraction processes, and in-depth analyses of animal activity. Through the provision of these specialised facilities, PTRL aims to support and facilitate a wide spectrum of scientific research endeavours, contributing to the advancement of knowledge and innovation across various disciplines.